IL-17 and IL-6 as Inflammatory Response in a Case of Neurobrucellosis Presenting as Leucoencephalopathy - Kchaou, Mariem; Belghith, Meriam; Bahrini, Khadija; Maghrebi, Olfa; Mekki, Najla; Belal, Samir; Barbouche, Mohamed Ridha (Archives of Clinical and Medical Case Reports, 2019)
Brucellosis is a zoonotic infection caused by Gram-negative intracellular bacteria. It is an ongoing public health problem in many countries throughout the world, especially in the Mediterranean region. Involvement of the central nervous system, particularly the white matter, is relatively uncommon and the underlying mechanism is steel unclear. We describe here, the case of a young woman presenting Neurobrucellosis as a leucoencephalopathy, and discuss the physiopathogeny through immunological findings. An extensive investigation of her immune system showed no defect in NADPH oxidase complex and no functional disorder of IL12/IFN-γ pathway. Quantitative real-time PCR analysis, preceding and following antibiotic treatment, revealed the association of inflammation in the cerebro-spinal fluid with higher IL-6 and IL-17 expression. These results could improve our understanding of inflammation in a leptomeningial and WM involvement related to Neurobrucellosis for a better diagnosis when clinical, MRI data and hematological routine tests are non-specific.